From pre-school to university: student-teachers’ characterize their EFL writing development - Viáfara Gozález, John Jairo (Colombian Applied Linguistics Journal, 2008)
A historical review of approaches used to support students’ writing in English as a foreign or second language , as well as of Colombian teachers’ efforts to guide their pupils’ in this area becomes the starting point for this qualitative research. The study explores the biographical narratives of EFL pre-service teachers from Universidad Pedagógica y Tecnológica de Colombia (UPTC) to describe how they have developed their writing in English. The research reveals the methodological practices to which participants have been exposed from their early schooling until their university education in Colombian institutions, most of them located in Boyacá. Finally, the pedagogical implications seek to provide reflective points for the education of in-service and pre-service teachers at a time when higher standards in students’ foreign language learning are expected.